Evaluation of cracking resistance of Superpave mixtures in Kansas - Aziz, Syeda Rubaiyat (Kansas State University, 2013)
Reclaimed Asphalt Pavement (RAP) is a useful alternative to virgin aggregates in hot-mix asphalt (HMA) as it reduces cost, conserves energy, and enables reuse of existing asphalt pavement. However, use of higher percentage of RAP sometimes leads to drier mixes that are often susceptible to early cracking. In this study, cracking resistance of Superpave mixtures with varying asphalt and RAP contents were investigated. HMA specimens were prepared based on Superpave mix design criteria for 12.5-mm (1/2-inch) nominal maximum aggregate size (NMAS). Specimens were compacted using the Superpave gyratory compactor. Static and repeated semi-circular bending (SCB) tests and Texas overlay tests (OT) (TEX-248-F) were performed in order to evaluate cracking resistance of Superpave mixtures containing three different asphalt contents (5.2%, 4.9%, and 4.6%) and three RAP percentages (20%, 30%, and 40%) from two distinct sources. Results from both crack tests showed that, with decreased asphalt content, cracking propensity increases. In general, higher percentage of RAP decreases cracking resistance. Statistical analysis of the results indicated a strong positive correlation between the asphalt film thickness and the number of load cycles before failure. Comparison of mean test results suggested that the Texas overlay test could do better evaluation of cracking resistance than the R-SCB test. This study was limited to mixtures with two sources of RAP. Because of such limitations and conflicting results from these RAP sources, a general conclusion regarding the minimum binder and maximum RAP contents without compromising cracking resistance could not be made. However, separate conclusions were drawn depending upon the characteristics of the RAP source.
Keywords: Asphalt pavements; Cracking resistance; Semi-circular bending test; Texas overlay test; RAP; Civil Engineering (0543)